Experimental study on dynamic response of smooth and straked risers in tandem arrangement coupling interference effect. (January 2020) - Li, Peng; Li, Quan; Liu, Yu; Wang, Yu; Guo, Haiyan; Zhang, Yongbo
Abstract: An experiment was conducted in a combined wave–current water flume on two tandem risers subjected to uniform flow. The riser model has an effective length of 2.0 m. The aspect ratio is 111.11. The upstream riser is smooth and the downstream riser fitted with three-strand helical strakes with pitch 17.5 D and height 0.25 D . By varying the external flow velocities and spacing ratios, through comparisons with the dynamic response of isolated smooth and isolated straked riser, the paper observe how interference effect impacts the dynamic characteristics and dynamic response of two risers in tandem arrangement, reveal how the suppression efficiency of the three-strand helical strakes responds to spacing ratio and external flow velocity, and explore the wake excitation effect of inter-riser fluids on the downstream riser and their dynamic feedback to the upstream riser. The results show that the dominant frequency of the upstream smooth riser is sensitivity to the change of the spacing ratio is low, and the displacement response is offset or enhanced in different degree due to the difference of the interference efficiency. The downstream straked riser dominates frequency and displacement higher than the isolated straked riser. The wake vortex of the upstream smooth riser acts on the downstream riser, occupying a dominant position in the vibration of the downstream riser. It degrades the vibration suppression efficiency of the three-strand helical strakes: the suppression efficiency is the highest at spacing ratio of 8, being a merely 70.57%. With the increase of the spacing ratio, the CF displacement of the riser gradually decreases, and the IL displacement gradually increases. The interference efficiency partition and suppression efficiency at different spacing ratios reflects the dynamic feedback of the upstream smooth riser is much smaller than the interference effect of the downstream suppression riser. Highlights: Analyze how interference effect impacts the dynamic response of two risers in tandem. Downstream straked riser had higher vibration amplitude than isolated straked riser. Greater spacing ratio, higher CF suppression efficiency of downstream straked riser. Greater spacing ratio, smaller IL suppression efficiency of downstream straked riser.